The Influence of Employer Branding and Employee Value Proposition on Employee Engagement and Retention at Qara’a Technology Startup - Usman, Maharani; Karsim; Mufrihah, Mazayatul; Shalahuddin, Ahmad; Hasanudin (Yayasan Sinergi Kawula Muda, 2025)
In a competitive business environment, the ability to attract and retain quality talent is critical to the success of startup companies. This study explores the role of employer branding and employee value proposition (EVP) on employee engagement and retention in startup companies in Pontianak City. This research uses a qualitative approach with data collection methods through in-depth interviews, participatory observation, and document analysis to measure their perceptions of Employer branding and EVP practices and their impact on engagement and retention levels. The results of this study reveal that Qara'a's startup employer branding, based on the dimensions of interest value, social value, economic value, development value, and application value, can increase employee engagement and retention. Furthermore, the application of Qara'a's employee value proposition is packaged attractively and by employee expectations so that the EVP can increase the engagement and retention of Qara'a startup employees.